2018
DOI: 10.3389/fimmu.2018.02582
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics in Cancer Immunobiology: The Future of Precision Oncology

Abstract: Cancer is a heterogeneous and complex disease. Tumors are formed by cancer cells and a myriad of non-cancerous cell types that together with the extracellular matrix form the tumor microenvironment. These cancer-associated cells and components contribute to shape the progression of cancer and are deeply involved in patient outcome. The immune system is an essential part of the tumor microenvironment, and induction of cancer immunotolerance is a necessary step involved in tumor formation and growth. Immune mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 210 publications
0
37
0
Order By: Relevance
“…This technology holds the promise to uncover new information about the pathophysiology of complex disease states in high detail. Initial efforts in this direction with human material have focused on cancer (4,(19)(20)(21), although examples in other diseases are emerging (22,23) including one example of identification of a PBMC repertoire associated tuberculosis progression (2) and a second related to survival in acute infectious disease based on analysis of ~100 cells from 2 patients (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology holds the promise to uncover new information about the pathophysiology of complex disease states in high detail. Initial efforts in this direction with human material have focused on cancer (4,(19)(20)(21), although examples in other diseases are emerging (22,23) including one example of identification of a PBMC repertoire associated tuberculosis progression (2) and a second related to survival in acute infectious disease based on analysis of ~100 cells from 2 patients (3).…”
Section: Discussionmentioning
confidence: 99%
“…Single cell transcriptomic approaches continue to modify and expand our understanding of the function and classification of PBMC subsets (2,3). The degree to which these sophisticated approaches will lead to clinically actionable information remains to be established (4). To that end, we here took an integrated approach combining plasma cytokine quantification, flow cytometry, and single cell transcriptomics to address the challenging question of why some patients survive on VA-ECLS while many do not.…”
Section: Introductionmentioning
confidence: 99%
“…Among non-malignant cells, we found that non-neuroblastoma samples have a higher proportion of infiltrating immune cells compared with neuroblastoma samples, especially cytotoxic T-cells. Cytotoxic T-cells are a key player in tumor surveillance and inhibition of tumor growth by secreting cytokines as well as perforin or Fas-mediated cytotoxic response 47 . Therefore, it is an important target of immunotherapy and considered as an important prognostic indicator in many cancers, including neuroblastoma 29,48 .…”
Section: Pntsmentioning
confidence: 99%
“…We have previously demonstrated that tumour infiltrated myeloid-derived suppressor cells (MDSCs) are involved in the formation of lung metastasis in PyMT/ELF5 alveolar tumours 15 . As tumour infiltrated myeloid cells constitute a low abundance population 51 we kept it as a unique cell cluster, however, our scRNAseq analysis was able to map the cellular mechanism for MDSC expansion, recruitment and malignant activation previously described in these alveolar tumours 52 , identifying the cell of origin of well-known signalling pathways involved in this process (Fig. 7D).…”
Section: Characterisation Of the Cell-to-cell Interactions Involved Imentioning
confidence: 99%